Effects of ethanol extract of Salvia hydrangea on hepatic and renal functions of streptozotocin-induced diabetic rats - Ali Zarei; Gholamhassan Vaezi; Ali Akbar Malekirad; Mohammad Abdollahi (Mashhad University of Medical Sciences, 2015)
Objectives: A wide range of liver and kidney disorders are associated with diabetes and there is a mutual relationship between diabetes and these diseases. Herbal medicine with having abundant ingredients is one of these options. The goal of this study was to compare the effects of alcoholic extract of aerial parts of Salvia hydrangea with glibenclamide on functional tests of liver and kidney in diabetic rats induced by streptozotocin. Materials and Methods: In this study, 35 male Wistar rats were divided into five groups (n= 7 in each group): control, diabetic control, and three experimental diabetic groups. The controls had normal access to water and food, the diabetic control group was given drug solvent and the three experimental groups received ethanol extract of Salvia hydrangea at doses of 100 and 200 mg and glibenclamideat a dose of 10 mg/kg/BW by gavage, respectively. To induce diabetes, a single dose of streptozotocin (60 mg/kg/BW) was injected to rats intraperitoneally. Blood samples were collected at day 21 from all groups and the related blood factors were measured and analyzed. Results: The results showed that the levels of creatinine, urea, aspartate aminotransferase (AST), and fasting blood sugar (FBS) in all diabetic groups increased compared to the control group. In all experimental groups and the group which received glibenclamide,a significant decrease was shown compared to the diabetic group (p